Assessing the Effects of Tourism Revenue Sharing to the Improved Livelihood to the Neighboring Communities of Bwindi: A Case Study of Uhoma Sector. - Mutungyirehi, Dan (Kabale University, 2023)
The purpose of this study was to assess the effects of tourism revenue sharing to the improved livelihood to the neighboring of communities of Bwindi. The study used both qualitative and quantitative approaches. The sample size of 178 respondents was used selected from a total population of 300. Purposive Sampling and simple random sampling were adopted for this study. Questionnaire and interviewing methods were used as data collections methods. The findings revealed that 81.9% of the respondents stated that they had benefited from revenue sharing scheme, while 18.1 % of the respondents stated that they had not benefited from revenue sharing. Findings therefore indicated that majority of the respondents had benefited from the revenue sharing. The study recommends that Uganda wildlife staff should always engage community political leaders, so that they involve other stake holders in conservation.